2018
DOI: 10.1177/0363546518777732
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Preoperative Knee Hyperextension Is a Predictor of Failure in an Anterior Cruciate Ligament Revision Cohort: A Report From the MARS Group

Abstract: This study revealed that preoperative physiologic passive knee HE ≥5° is present in one-third of patients who undergo revision ACLR. HE ≥5° was an independent significant predictor of graft failure after revision ACLR with a >2-fold OR of subsequent graft rupture in revision ACL surgery. Registration: NCT00625885 ( ClinicalTrials.gov identifier).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Clinical research studies have shown conflicting results. Several studies have shown an association between knee hyperextension and preoperative instability, 4 , 43 postoperative instability, 56 and graft failure, 8 while others report no relationship between hyperextension and risk of laxity or rupture. 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical research studies have shown conflicting results. Several studies have shown an association between knee hyperextension and preoperative instability, 4 , 43 postoperative instability, 56 and graft failure, 8 while others report no relationship between hyperextension and risk of laxity or rupture. 7 …”
Section: Discussionmentioning
confidence: 99%
“…Clinical research studies have shown conflicting results. Several studies have shown an association between knee hyperextension and preoperative instability, 4,43 postoperative instability, 56 and graft failure, 8 while others report no relationship between hyperextension and risk of laxity or rupture. 7 High-grade preoperative knee laxity, as determined by a grade 3 Lachman or pivot-shift test result, was significantly associated with 3-times greater odds of graft rupture within the Stability 1 Study, although it was not retained in the asymmetric pivot-shift model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] Another multicenter study showed that knee recurvatum by more than 5° is a significant independent predictor of ACL graft failure. [22] Vaishya and Hasija reported that joint hypermobility is more common in patients with ACL injury than in control groups. [23] In a prospective study of 1558 athletes, Myer et al [11] reported that the presence of knee hyperextension beyond neutral resulted in a five-fold higher risk of ACL injury, taking into account the GJH measurements.…”
Section: Discussionmentioning
confidence: 98%
“…22 (IBM SPSS Statistics for Windows, Armonk, NY; IBM Corp., Released 2013). First, a Kolmogorov-Smirnov test was used to determine which variables should be included in the data analysis and whether the data for the variables were normally distributed.…”
mentioning
confidence: 99%